Pengaruh Perceived Value Dan Brand Image Terhadap Keputusan Pembelian Yang Berdampak Pada Kepuasan Konsumen Teras Depan Kopi Cipete Jakarta Selatan - Adelia Aribah; Ade Yusuf (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study is a quantitative research with an associative approach aimed at analyzing the influence of perceived value and brand image on purchase decisions and their impact on consumer satisfaction at Teras Depan Kopi, Cipete, South Jakarta. Data were collected through questionnaires distributed to customers who had made purchases, and then analyzed using the SEM-PLS method. The inner model results show an R-square value of 0.676 for Purchase Decision and 0.592 for Consumer Satisfaction, indicating that the model has good predictive capability.Partially, brand image has a positive and significant effect on Purchase Decision (coefficient 0.681; T-statistic 12.819; p-value 0.000) and Consumer Satisfaction (coefficient 0.440; T-statistic 3.622; p-value 0.000). Perceived value also has a positive and significant effect on Purchase Decision (coefficient 0.193; T-statistic 3.170; p-value 0.002), but does not significantly affect Consumer Satisfaction. In addition, Purchase Decision has a positive and significant effect on Consumer Satisfaction (coefficient 0.272; T-statistic 2.135; p-value 0.033). The indirect effect results indicate that Purchase Decision mediates the relationship between brand image and Consumer Satisfaction, but does not mediate the relationship between perceived value and Consumer Satisfaction. Overall, brand image and perceived value play important roles in improving purchase decisions, which in turn contribute to enhancing consumer satisfaction